EXPLORING THE IMPLEMENTATION OF TRANSLANGUAGING APPROACH IN BILINGUAL SCHOOL: A CASE STUDY - Ramadhani, Dita Ariyantika; Achmad, Sarifah; Armanda, Muhamad Laudy (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
The necessity to promote multilingualism and cultural competence in educational settings has grown substantially in our contemporary globalized society. The phenomenon is referred to the translanguaging approach, and it is commonly applied in bilingual schools. This approach has been implemented in various contexts, particularly in English for Young Learners (EYL) programs. However, study on translanguaging as it applies to elementary-level bilingual education remains scarce. The issue lies in the traditional segmentation of languages in bilingual education systems, which frequently disregards the possible advantages of utilizing the complete linguistic repertoire of students. The main objective of this study is to investigate the efficacy of a translanguaging approach within a particular bilingual elementary school setting. Data will be collected via a qualitative case study method that includes student feedback, teacher interviews, and classroom observations. This research approach intends to provide valuable insights into the practical aspects and obstacles associated with the implementation of translanguaging practices. Insights from teacher interviews revealed the benefits of translanguaging in a bilingual environment. In addition to contributing to the ongoing discussion on effective language pedagogy, this study emphasizes the significance of embracing linguistic diversity in EYL.